Dependence of Indicators of Daily Blood Pressure Monitoring on Activity of Pathological Process in Patients with Systemic Lupus Erythematosus - Abrahamovych O.; Abrahamovych U.; Kushyna A.; Guta S.; Synenkyi O. (Львівський клінічний вісник)
Introduction. It is known that the course of systemic lupus erythematosus (SLE) is often accompanied by the syntropic lesions of the cardiovascular system, among which hypertension has a significant role. Being an important risk factor for the emergence and growth of the severity of syntropic cardiovascular complications in patients with SLE, especially in its active phase, hypertension often impairs their quality of life, and at times is the main cause of death. The purpose of the study is to discover the dependence of the parameters of daily blood pressure monitoring (DMAT) on the pathological process activity in patients with SLE. In order to achieve this objective our goals were to evaluate the following DMAT parameters in SLE patients depending on the pathological process activity: 1) blood pressure in SLE patients during the period of 24 hours; 2) blood pressure in SLE patients during the active and passive periods. Materials and research methods. In a rheumatology centre of Danylo Halytsky Lviv National Medical University at Lviv regional clinical hospital in a randomized manner were examined 83 patients (71 women and 12 men aged 1768) diagnosed with SLE, who afterwards were stratified into three groups according to the pathological process at the time of DMAT: with the activity of degree I (25 women and 5 men, average age 42,9 ± 2,1 years, with the activity of degree II (33 women and 6 men, the average age 37.9 ± 1,8 years), with the activity of degree III (13 women and 1 men, average age 37.9 ± 1,8 years). The control group consisted of 35 practically healthy individuals of the same sex and age. DMAT was performed with the use of the apparatus ABPM-04 (company “Meditech”, Hungary), the monitor was being activated every 15 minutes during the daytime (from 6 a.m. till 9:59 p.m.) and every 30 minutes during the nighttime (from 10 p.m. till 5:59 a.m.). According to the first goal was rated the BP in the SLE patients during the period of 24 hours, for which: a) were examined the average daily, maximum and minimum levels of systolic blood pressure (SBP), diastolic blood pressure (DBP), the average blood pressure; b) was analysed the daily index (DI) of SBP, DBP and the average blood pressure; c) was examined the time index (TI) of SBP, DBP and the average blood pressure. According to the second goal was rated the blood pressure in SLE patients during the active and passive periods, for which: a) were examined the average daily, maximum and minimum levels of SBP, DBP, the average blood pressure during the active period; b) were examined the average daily, maximum and minimum levels of SBP, DBP, the average blood pressure during the passive period; c) was studied the TI of SBP, DBP and the average blood pressure during the active and passive periods. Were compared the DMAT indices in patients with different degrees of activity of SLE: patients with the SLE activity of degree I were compared with the patients with the SLE activity of degree II and III, patients with the SLE activity of degree II were compared with the patients with the SLE activity of degree III. The actual material was processed on a PC with the help of Microsoft Excel using descriptive statistics and Student’s t-test in order to compare the samples with a normal distribution. For all the examined patients were applied the principles of the Helsinki Declaration of Human Rights, the European Convention on Human Rights and Biomedicine. Results of the investigation and their discussion. After the indices of blood pressure in patients with SLE were compared during the day in general, was stated the availability of the increase of blood pressure with the increase of the degree of the SLE activity on almost all indicators (except the maximum DBP). This pattern of the consistent growth, depending on the severity of the disease, was proved by the results of average estimation of daily SBP, minimum SBP, average daily DBP, minimum DBP, daily and minimum average blood pressure. Of all the indicators which are characterized by the increase of blood pressure in patients with the SLE with the activity of degree II compared with patients with the SLE with the activity of degree III, the indices of average SBP are accurate. The most convincing information, that truly confirms the increase of blood pressure with the increase of the SLE activity, was detected in patients of the third group comparing seven out of nine (except the maximum DBP and SBP, the results of which are unreliable) indicators of SBP, DBP and the average blood pressure with the patients of the second (except the maximum SBP, the level of which varies, but not significantly) and the first groups. Since DI is a significant indicator that shows a violation of the circadian rhythm of blood pressure due to its insufficient decline during the night period, the obtained results can be interpreted as a sign that an increase in the activity of SLE increases the severity of a violation of circadian rhythm changes in blood pressure with a decrease in the number of patients with preserved physiological rhythm, increase of the deficit of blood pressure reduction during a passive period and the increase in the number of the so-called “night-peakers” patients with the phenomenon of “non-dipper”, which may indicate a malignant course of hypertension, the presence of its symptomatic form and is considered to be an independent risk factor of cardiovascular complications. The obtained results of TI studies show, that with the increase of the SLE severity the frequency of episodes in which the blood pressure exceeded the permissible limits, was increasing. All the nine indicators, that characterize the blood pressure during the active period, investigated in patients with I, II and III levels of activity, increased naturally (except the maximum DBP in the third group) with the increase of the degree of SLE activity, and the most directly-proportional dependence of the increase of the severity of disease and the value of the investigated parameters is observed in the III group patients compared with the II and especially the I group patients. All the nine indicators, that characterize the blood pressure during the passive period, investigated in patients with I, II and III levels of activity, increased naturally with the increase of the degree of SLE activity, and the most directly-proportional dependence of the increase of the severity of disease and the value of the investigated parameters is observed in the III group patients compared with the II and especially the I group patients. Out of the six parameters of TI in patients of the three groups only the SBP TI was below the reference parameters in patients of the first group with the SLE activity of degree I during the active period and all three indices in patients within this group (SBP, DBP and the average blood pressure) are higher during the passive period than during the active. All the six indicators characterizing the TI during both active and passive periods naturally increase with increase of the degree of activity of SLE, and most clearly a directly-proportional dependence between the increase of the severity of disease and the value of the investigated parameters is observed in the III group patients compared with the II and especially the I group patients. Conclusions. In patients with SLE the indices of DMAT depend on the activity of the pathological process – the blood pressure increases significantly with its rise on almost all parameters (except the maximum DBP), with the change of the physiological circadian rhythm due to its insufficient decline in the night period and with an increase of frequency of episodes in which the blood pressure exceeds the permissible limits. The identified patterns of changes of DMAT are also preserved throughout the period of 24 hours, and according to the results of their separate evaluation during a nighttime and daytime so that during a passive periods these figures are significantly more often lower than the reference values, especially in patients of first and second groups.